Em defesa da categoria de voz média no português - Camacho, Roberto Gomes [UNESP] (Pontifícia Universidade Católica de São Paulo (PUC-SP), 2003)
A voz média representa uma categoria flexional das línguas clássicas indo-européias com a função de expressar estados de coisas que afetam o sujeito do verbo ou seus interesses. O português dispõe de um conjunto de predicados, formalmente identificados pelo uso anafórico e não-correferencial do pronome 'se', em que se sustenta a noção de diátese medial. Este trabalho pretende fornecer evidências formais, semânticas e tipológicas para postular uma distinção entre construções médias e reflexivo-recíprocas.

Middle voice represents an inflexional category of classical Indo-European languages with the function of expressing states of affairs which affect the subject of the verb or its interests. In Portuguese there is a set of predicates, formally identified by an anaphorical but non-coreferential use of the pronoun 'se', which supports the notion of middle diathesis. This paper aims at providing formal, semantic and typological evidences in order to postulate a distinction between middle and reflexive-reciprocal constructions.
In defense of the middle voice category in Portuguese
Keywords: Voz; Diátese; Voz Média; Voz Reflexivo-recíproca; Voice; Diathesis; Middle Voice; Reflexive-reciprocal Voice